2023
DOI: 10.3389/fneur.2023.1174711
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of inflammatory markers for in-hospital mortality in intensive care patients with acute ischemic stroke: a retrospective observational study based on MIMIC-IV

Abstract: BackgroundAcute ischemic stroke (AIS) is a primary cause of death and disability worldwide. Four markers that can be readily determined from peripheral blood, namely, the systemic immune-inflammation index (SII), neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and total bilirubin, were measured in this study. We examined the relationship between the SII and in-hospital mortality after AIS and evaluated which of the above four indicators was most accurate for predicting in-hospital mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…In most research on ischemic stroke patients using the MIMIC database, the selection of cases is overly broad. Many studies indiscriminately include all patients coded under ICD-9: 433, ICD-9: 434, ICD-9: 436, and ICD-10: I63 ( 25–28 ). However, half of these specific sub-codes, such as 433.00: Occlusion and stenosis of the basilar artery without mention of cerebral infarction, 433.10: Occlusion and stenosis of the carotid artery without mention of cerebral infarction, 433.20: Occlusion and stenosis of the vertebral artery without mention of cerebral infarction, and 433.30: Occlusion and stenosis of multiple and bilateral precerebral arteries without mention of cerebral infarction, do not necessarily diagnose an ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…In most research on ischemic stroke patients using the MIMIC database, the selection of cases is overly broad. Many studies indiscriminately include all patients coded under ICD-9: 433, ICD-9: 434, ICD-9: 436, and ICD-10: I63 ( 25–28 ). However, half of these specific sub-codes, such as 433.00: Occlusion and stenosis of the basilar artery without mention of cerebral infarction, 433.10: Occlusion and stenosis of the carotid artery without mention of cerebral infarction, 433.20: Occlusion and stenosis of the vertebral artery without mention of cerebral infarction, and 433.30: Occlusion and stenosis of multiple and bilateral precerebral arteries without mention of cerebral infarction, do not necessarily diagnose an ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Existing literature has highlighted a link between elevated SII levels and an increased risk of mortality both in the general population and among individuals with conditions characterized by significant inflammatory processes 28 31 . Regarding the acute ischemic stroke in intensive care units, one study identified a positive, albeit non-linear, relationship between SII and in-hospital mortality 11 , as well as in individuals with stroke-associated pneumonia 32 . Furthermore, research has shown that SII is associated with a heightened risk of mortality in adults with asthma 33 .…”
Section: Discussionmentioning
confidence: 99%
“…It is derived from a formula incorporating levels of specific immune system markers obtained from complete blood counts, specifically, (platelets × neutrophils) / lymphocytes 7 . Traditionally, SII has been utilized as a mortality predictor for patients with various tumors 6 , 7 , 34 , 36 , cerebrovascular diseases 8 , 9 , 11 , and cardiovascular conditions 9 , 10 , 12 . The scope of SII's application has been broadening, with recent research indicating its potential in forecasting disease severity and monitoring the efficacy of treatments 13 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Presently, IDRs are extensively utilized across a diverse spectrum of medical disciplines as a dependable and conveniently accessible metric for gauging the immune reaction to a range of both infectious and noninfectious triggers. These ratios are subject to the influences of numerous factors, encompassing variables like diabetes, obesity, psychiatric disorders, solid organ malignancies, sepsis, pharmaceutical interventions, acute and chronic vascular disease, including coronary heart disease and stroke, and viral infections such as the SARS-CoV-2 virus [21,22]. Our analysis suggests that the preoperative values of three of the IDRs-namely, NLR, SII, and PLR, respectively-are elevated in POGD patients and seem to positively correlate with the duration of intestinal paresis, as assessed by the Tf, TL, and NGtR.…”
Section: Discussionmentioning
confidence: 99%